Curing the Dutch disease: The role of tariffs - Cece Cherif Delamou (Journal of Government and Economics)
This study explores the role of tariffs in addressing the Dutch Disease effect in resource-rich developing economies. By developing a theoretical framework built on existing literature, the study explores the role that the structure of taxes, internationally, can play in mitigating the adverse effects of resource exports on domestic industrial activity. The theoretical analysis finds that tariffs do influence domestic intersectoral labor allocation as well as industrial production in a resource-exporting economy and can counterbalance the effects of resource exports. Empirical data from 40 developing economies (2004–2021) confirms a negative relationship between resource dependence and manufacturing share of labor, and corroborates the theoretical finding that tariffs do reduce this impact.